2013
DOI: 10.1097/ftd.0b013e3182804c9b
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sensitive Phospho-p70 S6 Kinase ELISA to Quantify mTOR Proliferation Signal Inhibition

Abstract: Background: Drug blood levels can only serve as a surrogate because of the lack of information on the drug's direct pharmacological effects in the individual patient. Measurement of the mammalian target of rapamycin (mTOR) activity dependent on the phosphorylation status of p70 S6 kinase (p70 S6K) offers a practical way for monitoring pharmacodynamic drug activity, with the potential to better assess the state of immunosuppression in individual patients. Material and Methods:Here, we established a novel in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…In similarity to previous reports reports by Hartmann et al [11] and by Hoerning et al [13] (both groups using a PD assay based on anti-p-p70S6K) there was no correlation between the read out in our assay and the whole blood concentrations of either Evr or Sir.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In similarity to previous reports reports by Hartmann et al [11] and by Hoerning et al [13] (both groups using a PD assay based on anti-p-p70S6K) there was no correlation between the read out in our assay and the whole blood concentrations of either Evr or Sir.…”
Section: Discussionsupporting
confidence: 93%
“…Western blot analysis in the reference laboratory was performed as previously described [11]. Briefly, 40 g of protein from lysed PBMCs was subjected to SDS (sodium dodecyl sulfate) polyacrylamide gel electrophoresis and then electrotransferred to a Hybond P membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In this situation, some working groups have launched proposals for the advanced validation of specific methodologies, for example, the International Council for Standardization in Hematology (ICSH) and International Clinical Cytometry Society (ICCS) practice guidelines for assays and instrumentation regarding flow Compared with other candidate biomarkers in the field of immunosuppression, drug-specific pharmacodynamic biomarkers seem to be more carefully validated, or at least information on their validation is more frequently made available. 25,91,105,106 An issue of particular importance for the validation of all biomarker assays to be used with clinical samples is the setting of appropriate acceptance criteria for their analytical performance. As mentioned above, this step is critical for the performance of a biomarker during the clinical qualification.…”
Section: Analytical Performance and Methods Validationmentioning
confidence: 99%
“…mTOR inhibition results in the dephosphorylation and inactivation of the downstream effector p70 S6 kinase (p70S6K). The phosphorylation status at the Thr389 site of the p70S6K was previously assessed in PBMCs of renal transplant recipients using Western blot [97,98], while recent studies explored other quantitative and applicable methods such as commercial enzyme-linked immunosorbent assay (ELISA) kit and phosphoflow cytometry [99,100]. Results showed that mTOR inhibition was associated with marked reduction of p70S6K phosphorylation but failed to correlate with mTOR inhibitor trough levels [97,98,100].…”
Section: Mtor Inhibitorsmentioning
confidence: 98%